1997
DOI: 10.1007/s002130050188
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus properties of the nicotinic agonist cytisine

Abstract: Cytisine binds with high affinity and specificity to neuronal nicotinic receptors but its physiological and behavioural effects are complex and differ from those of nicotine. The present study explores the behavioural aspects further by comparing the discriminative stimulus effects of cystisine with those of nicotine. Two groups of rats were trained to discriminate cytisine (2 mg/kg s.c.) or nicotine (0.2 mg/kg s.c.) from saline in a two-lever operant conditioning procedure with food reinforcers presented on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…However, mecamylamine was less effective at blocking the small cardiovascular changes produced by cytisine. Although previous findings have reported that the in vitro and in vivo effects of cytisine were partially or fully attenuated by mecamylamine (Stolerman et al, 1983; Hall et al, 1993; Chandler and Stolerman, 1997; Cunningham and McMahon et al, 2011; Cunningham et al, 2012), the current data suggest that the large doses of cytisine used in the present study have some non-nicotinic receptor-mediated effects.…”
Section: Discussioncontrasting
confidence: 90%
“…However, mecamylamine was less effective at blocking the small cardiovascular changes produced by cytisine. Although previous findings have reported that the in vitro and in vivo effects of cytisine were partially or fully attenuated by mecamylamine (Stolerman et al, 1983; Hall et al, 1993; Chandler and Stolerman, 1997; Cunningham and McMahon et al, 2011; Cunningham et al, 2012), the current data suggest that the large doses of cytisine used in the present study have some non-nicotinic receptor-mediated effects.…”
Section: Discussioncontrasting
confidence: 90%
“…However, the current findings highlight the importance of nAChRs besides α4β2* in the behavioral effects of varenicline, which is the most effective smoking cessation aid on the market today (Hays et al 2008). Previous studies using either multiple nicotine training doses (Jutkiewicz et al 2011; Cunningham and McMahon 2013) or cytisine as a training drug (Chandler and Stolerman 1997) have strongly implicated a role for multiple nAChR subtypes in the discriminative stimulus effects of nicotine, and failure of DHβE to antagonize varenicline in the nicotine discrimination is consistent with a possible contribution of non-α4β2* nAChRs to the discriminative stimulus effects of nicotine.…”
Section: Discussionmentioning
confidence: 85%
“…However, unlike varenicline, cross-tolerance failed to develop from nicotine to cytisine. While differences in the receptor pharmacology of nicotine and cytisine have been previously observed in vivo (Chandler and Stolerman, 1997), antagonism of cytisine by mecamylamine suggests that nAChRs mediate the rate-decreasing effects of cytisine. The lack of cross-tolerance from nicotine to cytisine could indicate that the current parameters of chronic nicotine dosing do not produce loss of function at the nAChR subtypes that mediate the effects of cytisine.…”
Section: Discussionmentioning
confidence: 86%